Critical reading and writing for postgraduates - Wallace, Mike; Wray, Alison (Sage study skills, 2016)
"Reading critically, and writing using critical techniques, are crucial skills you need to apply to your academic work. Practical and engaging, Critical Reading and Writing for Postgraduates is bursting with tools for analysing texts and structuring critical reviews, helping you to gradually build your skills beyond undergraduate level and gain confidence in your ability to critically read and write." -- Provided by publisher.